Robust snubberless soft-switching power converter using SiC power MOSFETs and bespoke thermal design - Giuliani, F.; Dipankar, D.; Delmonte, N.; Castellazzi, Alberto; Cova, P. (Elsevier, 2014)
A number of harsh-environment high-reliability applications are undergoing substantial electrification. The converters operating in such systems need to be designed to meet both stringent performance and reliability requirements. Semiconductor devices are central elements of power converters and key enablers of performance and reliability. This paper focuses on a DC–DC converter for novel avionic applications and considers both new semiconductor technologies and the application of design techniques to ensure, at the same time, that robustness is maximized and stress levels minimized. In this respect close attention is paid to the thermal management and an approach for the heatsink design aided by finite element modelling is shown.